If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2s + 6t = 8 Solving 2s + 6t = 8 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-6t' to each side of the equation. 2s + 6t + -6t = 8 + -6t Combine like terms: 6t + -6t = 0 2s + 0 = 8 + -6t 2s = 8 + -6t Divide each side by '2'. s = 4 + -3t Simplifying s = 4 + -3t
| 8x+3-2x=3x+12 | | 4+6x=40 | | 4y+13=2y+7 | | 5(3)-2y=-13 | | 7x^2=182 | | x/3=-4-(-3) | | 8-7x=78 | | -9+7x=-9 | | L(2w+5)=65 | | ((2x^2)4)-16=0 | | 3x-5x=14 | | w^2-27w+162=0 | | -6h+4-3+h=h | | 9x^2-12x=14 | | 120+20=150+15x | | 5x^2+3xy-2y^2=0 | | -2+5x=-17 | | q(x)=-x-2 | | 7g(2-6)=168 | | 2a-(-2c)= | | -8(10t+8)=8(10t-4) | | y^2+y^3-18=0 | | -u/9-8=-4 | | -3q=-12 | | 0.9x-0.4(6-2x)=-0.2(x-7) | | -92000+7000x=2000+800x | | -6x^2+8x-2=0 | | 3x-9=-45 | | 3x+20+x+32=80 | | -6=0.75u+12 | | 36-9w=75w+150 | | 1x-0.4x= |